Factors affecting the attitude of Turkish generation Y consumers toward U.S. Apparel Specialty Retailers - Savaş, Selen (My University, 2010)
TÜRKİYE’DEKİ Y KUŞAĞI’NIN AMERİKAN HAZIR GİYİM PERAKENDECİLERİNE KARŞI TUTUMUNU ETKİLEYEN FAKTÖRLER Bu çalışmanın odak noktası Türk tüketicilerin Amerikan hazır giyim perakendecilerine karşı tutumudur. Ürün özellikleri, mağaza imajı boyutları, kültürel özellikler bakımından Amerikan ürünlerini sahiplenme, referans gruplar ve demografik özelliklerin Amerikan hazır giyim perakendecilerine karşı tutumuna (tekrar satın alma eğilimi, memnun olma, tavsiye etme, tercih etme) etkileri incelenmiştir. Çalışmanın örneklemi 1977-1994 arasında doğan Y Kuşağı’dır. Çalışma öncesinde Türkiye’deki hazır giyim sektörü ve Amerikan hazır giyim perakendecileri, Y kuşağının özellikleri ve alışveriş davranışları ile ilgili bir ön çalışma gerçekleştirilmiştir. Literatür taraması ile elde edilen bilgilerden sonra, birincil veri toplamak amacıyla anket çalışması yapılmıştır. Geliştirilen model doğrultusunda test edilerek incelenen ilişkiler çalışmada ortaya konulmuştur.

FACTORS AFFECTING THE ATTITUDE OF TURKISH GENERATION Y CONSUMERS TOWARD U.S. APPAREL SPECIALTY RETAILERS Main focus of this study is Turkish consumers’ attitude toward the US (apparel specialty) retailers. Therefore, the effects of product related attributes, store image dimensions, the adoption of US cultural products by means of acculturation characteristics, reference groups and the influence of demographic characteristics on Turkish consumers’ attitude (repurchase intention, satisfaction, advocacy and preference) towards the US (apparel specialty) retailers are examined. Generation Y, who were born between 1977-1994, is the sample population. Before designing the study, a pre-study, focusing on the Turkish apparel industry and US apparel specialty retailers in Turkey and characteristics and shopping behaviors of Generation Y consumers, was conducted. After gaining insight about the issues in the light of literature review, survey research is used to collect primary data. Based on the framework, the relations were tested and the whole relations are stated throughout the research.
Keywords: Hazır Giyim; Parekendecilik; Üretim Yönetimi